Mercury Inputs to Chinese Marginal Seas: Impact of Industrialization and Development of China. Issue 8 (15th August 2018) - Yin, Runsheng; Guo, Zhigang; Hu, Limin; Liu, Wenchuan; Hurley, James P.; Lepak, Ryan F.; Lin, Tian; Feng, Xinbin; Li, Xiangdong
Abstract: In the past decades, China has experienced substantial economic growth and industrialization. However, the effects of vast development of China on Hg input to the nearby oceans are still unclear. In this study, the influx and isotopic compositions of Hg in four 210 Pb‐dated sediment cores were examined to investigate changes in Hg deposition to the marginal seas off China over a century. Nearshore cores had higher Hg influxes than offshore cores. Increases of Hg influxes started since the 1950s, which coincides with China's economic development. Dramatic historical changes in Hg isotopic composition were observed in the cores (δ 202 Hg: −2.01‰ to −0.69‰; Δ 199 Hg: −0.16‰ to 0.31‰; n = 106). δ 202 Hg increased from the deep to the surface layers of the cores. The offshore cores mainly showed positive Δ 199 Hg values, but the pre‐1950 samples had more positive Δ 199 Hg values than the younger samples. The nearshore cores mainly showed negative Δ 199 Hg values in the pre‐1950s samples, but the younger samples showed Δ 199 Hg values close to zero. A triple‐mixing isotope model, used to quantify the contribution of potential Hg inputs (e.g., direct discharge of industrial Hg, soil Hg, and precipitation‐derived Hg), showed clear evidence of enhanced industrial Hg inputs to the ocean margin, but slightly decreased watershed soil Hg inputs in the last few decades. The variations of watershed‐derived Hg were likely caused by the construction of impoundments in major rivers of China. This study demonstrates that mercury inputs to Chinese marginal seas have been largely altered due to the industrialization and economic development of China. Plain Language Summary: This study demonstrates that mercury inputs to Chinese marginal seas have been largely altered due to industrialization and economic development of China with enhanced industrial Hg inputs to the ocean margin, but slightly decreased watershed soil Hg inputs in the last few decades. Key Points: The industrialization and hydrologic manipulation can largely alter the inputs of Hg to marginal seas Enhanced industrial Hg inputs to the ocean margin, but slightly decreased watershed soil Hg inputs in the last few decades Global industrialization has resulted in more inputs of industrial Hg